Pengaruh Independensi, Moral Reasoning dan Skeptisisme Profesional Auditor Terhadap Kualitas Audit: Studi Pada BPK-RI Perwakilan Jawa Barat - Bingky Aresia Landarica (Coopetition : Jurnal Ilmiah Manajemen, 2020)
The Objective from this research is to determine how much an Audit Quality can be affected from Auditor Independence, Moral reasoning and Auditor Professional Skepticism at Representative Audit Board of West Java Province. This research is using descriptive and verification approach as a method. The results of this study show that the higher the independence, moral reasoning and professional skepticism of the auditor can make higher the quality of the audit produced as well.